Coal gasification slag-derived hydrocalumite nanofluids for flow boiling heat transfer enhancement of power electronic devices - Junjie Wu; Junsheng Hou; Li Ma; Lei Huang; Zihan Ding; Hao Zhang; Baiqi Tian; Wenjing Zhou; Zhenzhen Chen; Nanjing Hao (Case Studies in Thermal Engineering)
With the development of the coal chemical industry, the production of coal gasification slag (CGS) is increasing, and the utilization is becoming challenging. Products of CGS utilization mainly include activated carbon, zeolites, silicon-carbon composites. However, the consumption of these products above is limited, which is insufficient to utilize the output thoroughly. As a result, it is urgent to expand the application area for large-scale and high-value utilization of CGS. CGS is rich in elements including aluminum and calcium, presenting a promising material for synthesizing nanofluids, which is promising for the thermal management of microelectronic devices. This study synthesizes hydrocalumite nanofluids from CGS and applies the nanofluids for flow boiling heat transfer experiment. Nanofluids with an average particle size of 50 nm are synthesized and applied to flow boiling heat transfer experiments. The critical heat flux (CHF) and the heat transfer coefficient (HTC) are improved by a maximum of 43 % and 52 %. Moreover, the fundamental principle of enhancement is discussed. Improved wettability, delayed bubble coalescence, additional nucleation sites are attributed to the improvement. This study not only presents a novel method for high-value utilization of CGS but also introduces a potential approach for thermal management enhancement of microelectronic devices.